FEMALE REPRESENTATION, CORPORATE GOVERNANCE, AND EARNING MANAGEMENT IN INDONESIAN NON-FINANCIAL FIRMS - Gunawan, Erick Teofilus; Sofian, Sofian; Wijaya, Hendra; Dwijayanti, S. Patricia Febrina (RIMA - Research In Management and Accounting, 2021)
This study analyzes the effect of female directors, managerial ownership, female audit committee, audit committee size, independent commissioners, board size on earnings management in Indonesian Non-Financial Firms.Â  The sample of this study consist of 291 non-financial firms over the period 2015-2017. This study measures earnings management using discretionary accruals. The data were analyzed using multiple regression. This study found that audit committee size negatively affects earnings management. This study also found that female directors, managerial ownership, female audit committee, independent commissioners, and board size do not affect earnings management. This study contributes to the important of audit committee as corporate governance mechanisms to reduce earnings management.